2004
DOI: 10.1097/00063110-200402000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of direct call to emergency medical services in acute myocardial infarction

Abstract: This study demonstrated that a call to the emergency medical services is underutilized by patients with symptoms of myocardial infarction, and documented the beneficial effects of an emergency medical services call by reducing pre-hospital delays and increasing early revascularization therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
2
12
1
1
Order By: Relevance
“…Previous studies showed that patients with a history of CAD could recognize the symptoms of MI and this promoted emergency medical system contact (3,14,15). However; in contrast to our expectation and also previous studies; presence of previous history of CAD or having cardiac risk factors was not associated with the ambulance usage in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies showed that patients with a history of CAD could recognize the symptoms of MI and this promoted emergency medical system contact (3,14,15). However; in contrast to our expectation and also previous studies; presence of previous history of CAD or having cardiac risk factors was not associated with the ambulance usage in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…Approximately one-half of the deaths attributed to ACS occur in the prehospital setting. has been shown to reduce delay in accessing definitive care (2)(3)(4)(5)(6)(7). Extension of care for ACS patients to the pre-hospital setting by EMS provides an opportunity for earlier initiation of evidence-based therapies, rapid access to aggressive treatment strategies, and coordination with capable centers for efficient delivery of care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the current recommendations, EMS underutilization by patients with ACS has been reported in different regions of the world (2,4,(12)(13)(14)(15)(16)(17). The reason for this has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The EMS may dispatch ambulance crews who are trained to detect and treat life-threatening complications at the accident scene and during transport. Several studies have shown that ambulance use may lead to greater and/or faster administration of early reperfusion therapy [13,14]. Regrettably, previous studies [15][16][17] indicated that almost half of AMI patients arrived at the hospital by other means than an ambulance.…”
Section: Introductionmentioning
confidence: 99%